Peran Suroboyo Bus Sebagai Upaya Peningkatan Ekonomi Hijau di Kota Surabaya - Zahra Al Madinah; Debby Nindya Istiandari (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
The population density in Surabaya City makes the needs of the community, one of which is transportation, high. Transportation has an important role in meeting the needs of the community in everyday life in the economic, socio-cultural and political fields. Unfortunately, this has led to traffic congestion. Thus, Surabaya City is trying to improve the public transportation system by launching environmentally friendly public transportation as an effort to implement a green economy, namely Suroboyo Bus. This research uses a qualitative method with a library research approach. Information was obtained from various institutional reports, scientific articles, websites, books, and related regulations. The focus of data acquisition sources is credible journal publishers. The results showed that congestion in Surabaya City was reduced due to the enthusiasm of the community to switch to public transportation compared to private vehicles to reduce greenhouse gas emissions. In addition, the Suroboyo Bus payment innovation by exchanging plastic bottles has succeeded in attracting the interest and awareness of some people in Surabaya City to manage plastic bottle waste, although there are still other complaints in the implementation of the policy. The role of Suroboyo Bus as an effort to improve the green economy can be said to be quite successful, but improvements still need to be made and the involvement of the government and the community so that Suroboyo Bus continues to be an environmentally friendly sustainable transportation.